RESULTS OF CYTOLOGICAL STUDY IN EXPERIMENTAL ANIMALS WITH AND WITHOUT TREATMENT OF ULCERATIVE NECROTIC GINGIVITIS WITH A COMPLEX OF DRUGS WITH ANTIOXIDANT PROPERTIES - Yu.H. Kilmukhametova; V.M. Batig; O.M. Soltys; I.I. Drozda; M.O. Ostafiichuk; N.V. Bernik (Український стоматологічний альманах)
Changes in the quantitative indicators of non-specific resistance systems of the body indicate a damage to homeostasis in the body and the development of a pathological process. The state of defense systems largely determines the course and provides a predictive characteristic of the intensity and effectiveness of treatment measures. In patients with inflammatory processes of periapical tissues, there is an imbalance of factors that characterize the state of local resistance of the oral cavity and the mucous membrane of the gums. Also, quantitative and qualitative changes in indicators of phagocytosis, chemotaxis of leukocytes, secretion of cytokines, immunoglobulins, and bactericidal activity of humoral factors of the body's defense were observed.